(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The approval of Constitutional Law no. 1/2022 “Amendments to Articles 9 and 41 of the Constitution on the subject of environmental protection” represents an opportunity to question the relationship between constitutional state and protection of future generations. In this perspective, after reconstructing the origins of the first “intergenerational references” in international law and their formal features, the essay dwells on the Italian context trying to clarify if and how the theme has influenced the interpretative and applicative dynamics concerning constitutional and primary norms, also in the light of the principles of “solidarity”, “intergenerational equity”, “sustainability” and “political accountability”.